2014
DOI: 10.1007/s13277-014-2925-6
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of long non-coding RNA MALAT1 correlates with tumor progression and poor prognosis in clear cell renal cell carcinoma

Abstract: Long noncoding RNAs (lncRNAs) have been investigated as a new class of regulators of cellular processes, such as cell growth, apoptosis, and carcinogenesis. LncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) has recently been identified to be involved in tumorigenesis of several cancers such as lung cancer, pancreatic cancer, and cervical cancer. However, the role of lncRNA MALAT1 in clear cell renal cell carcinoma (ccRCC) remains unclear. Expression levels of lncRNA MALAT1 in ccRCC tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
228
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(238 citation statements)
references
References 20 publications
6
228
0
2
Order By: Relevance
“…In previous years, due to the successful application of different novel approaches, including genome-wide gene expression screening, genome-wide association studies, region-targeted association assays and conventional linkage screening, designed LncRNA arrays, RIP-RNA sequencing, transgenic expression, and gene knockdown or knockout, the functions of LncRNAs in cancer are being increasingly characterized. Accumulating data show that several identified LncRNAs are crucial in tissue carcinogenesis, invasion and metastasis (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…In previous years, due to the successful application of different novel approaches, including genome-wide gene expression screening, genome-wide association studies, region-targeted association assays and conventional linkage screening, designed LncRNA arrays, RIP-RNA sequencing, transgenic expression, and gene knockdown or knockout, the functions of LncRNAs in cancer are being increasingly characterized. Accumulating data show that several identified LncRNAs are crucial in tissue carcinogenesis, invasion and metastasis (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, multiple studies reported that in different types of cancer there was abnormal expression of lncRNA, indicating that the same lncRNA may serve different functions in different types of cancer. For instance, a lncRNA named SPRY4 intronic transcript 1 (SPRY4-IT1) was reported to be overexpressed in melanoma, renal cell carcinoma, esophageal squamous cell carcinoma, breast cancer, bladder cancer and glioma, and associated with poor prognosis and promotion of tumor growth (24)(25)(26)(27)(28)(29). Certain studies also demonstrated that SPRY4-IT1 expression was decreased in non-small-cell lung cancer and gastric cancer, and acted with significant antitumor function in these two types of cancer (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that lncRNA expression profiles may act as biomarkers for diagnosis of ccRCC; lncRNA MALAT1, for example, was reported to be associated with tumor progression and poor prognosis in ccRCC (9), and lncRNA CADM1-AS1 was associated with poor prognosis in patients with ccRCC. Consistent with these findings, the current data revealed that the expression profiles of uc009yby.1 and ENST00000514034 had high sensitivity and specificity in distinguishing ccRCC from normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) interacts with enhancer of zeste homolog 2 and microRNA-205 to suppress the E-cadherin expression in RCC cells, suggesting that MALAT1 may offer a novel theranostic marker for RCC (8). An increasing number of studies have also demonstrated that certain lncRNAs are strongly associated with patient survival and early pathological changes in ccRCC (9,10). Recently, a large number of lncRNAs that have aberrant expression in ccRCC were screened via lncRNA microarray in several studies (11)(12)(13); however, the expression of these lncRNAs have not been further confirmed and their functions in ccRCC cells have not been explored.…”
Section: Introductionmentioning
confidence: 99%